Association between weight loss and clinical-pathologic factors in oncological patients in chemotherapy treatment: a longitudinal study - Débora Fernandes Pinheiro; Simone Carla Benincá; Caryna Eurich Mazur; Elisângela Meira; Jessica Wouk (Universidade Estadual de Maringá, 2019)
The present study aimed to evaluate the nutritional state and WL of individuals with cancer. Is a longitudinal observational study was performed with patients assisted in the oncological ambulatory. Sample was composed of 402 patients, with an average of 58.46±13.60 years old, 56.5% women and the majority elderly (51.74%). Regarding tumor localization, 12.9% were found in the head and neck, 22.6% in mamas, 10.2% in the lungs, 29.4% in the gastrointestinal tract (GI tract) and 29.4% in other body parts. A gradual fall of nutritional state in relation to BMI was observed, and the patients were advancing to malnutrition. When severe and not severe WL were correlated, a statistical difference was demonstrated regarding age, current and habitual weight, as well as the corresponding BMI (p<0.05).  Overweight and obese patients presented a higher severe WL than the other group (p<0.05). However, 67.34% of patients presented WL and a following nutritional state alteration, being cancer in the GI tract with a significant difference, 37.44% (p<0.05) with severe WL (p<0.000). Patients diagnosed with cancer, especially in the GI tract, treated with chemotherapy have higher chances of WL, which trigger a reduction of survival rate, being obesity and age reliable predictors of a consequent severe WL.